2018
DOI: 10.1021/acssuschemeng.8b02414
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Simultaneous Nitrogen and Phosphorus Removal Performance by Anammox–HAP Symbiotic Granules in the Attached Film Expanded Bed Reactor

Abstract: Dissolved nitrogen and phosphorus compounds are responsible for eutrophication and usually are treated by separate processes in wastewater treatment plants. In this study, the simultaneous, long-term, stable removal of phosphorus and nitrogen was achieved in a high-loading anammox attached film expanded bed (AAFEB) reactor. As an energy-saving and high-efficiency biological process, the anammox reaction performed stable and high nitrogen removal. In addition, the chemical environment and hydrodynamic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The abiotic reduction of NO − 2 by Fe(II) is an important N 2 O source in wastewater treatment and should not be ignored. Additionally, N 2 O emissions increased linearly during each phase (Figure 6), which was mainly due to the high sludge retention ability of the AAFEB reactor (Zhang, Ma, Lin, et al, 2018), resulting in the continuous accumulation of Fe(II). Therefore, N 2 O was formed chemically from Fe(II) and NO − 2 via abiotic reactions in this study.…”
Section: Effect Of Fe(ii) Accumulation On N 2 O Emissionmentioning
confidence: 98%
See 1 more Smart Citation
“…The abiotic reduction of NO − 2 by Fe(II) is an important N 2 O source in wastewater treatment and should not be ignored. Additionally, N 2 O emissions increased linearly during each phase (Figure 6), which was mainly due to the high sludge retention ability of the AAFEB reactor (Zhang, Ma, Lin, et al, 2018), resulting in the continuous accumulation of Fe(II). Therefore, N 2 O was formed chemically from Fe(II) and NO − 2 via abiotic reactions in this study.…”
Section: Effect Of Fe(ii) Accumulation On N 2 O Emissionmentioning
confidence: 98%
“…As shown in Figure 1, an AAFEB reactor with a working volume of 2.5 L, the same as that used in a previous study (Zhang, Ma, Lin, et al, 2018), was used in this experiment. The temperature of the reactor was controlled at 34 ± 2°C by a water jacket, while the outside of the reactor was covered with opaque foam to prevent the reactor from the effects of light.…”
Section: Reactor Setup and Operationmentioning
confidence: 99%
“…Previous experiences concerning simultaneous biological N oxidation or removal and biologically induced P precipitation within the same bioreactor in the framework of waste water treatment, aimed at promoting P recovery, are summarised in Table 3 [70][71][72][168][169][170][171][172] (an extended version of this table is provided as Supplementary Material). This approach allows simplifying the configuration of the treatment system.…”
Section: Phosphorus Recovery Experiences In Concomitant Configurationmentioning
confidence: 99%
“…Recent works conducted at Tohoku University (Japan) with anammox biomass in expanded bed reactors showed that, using synthetic substrate and under optimised bioreactor operation, simultaneous N removal and P uptake were feasible at rates as high as 16.7 g N L r −1 d −1 and 1. d −1 at 35 • C (using inner mineral cores of granules as biofilm carriers) [170]. A highly mineralised sludge grew within these reactors, with a relative volatile content that could fall down to values below 25% of the dry weight.…”
Section: Phosphorus Recovery Experiences In Concomitant Configurationmentioning
confidence: 99%
“…Recent works integrating anammox and CaPprecipitation reactions evidenced the feasibility of the formation of a dense HAP core wrapped by an external biofilm. 21,22 As a consequence, a highly mineralized sludge is produced within the bioreactor. Once this sludge is harvested, the high P content makes it an interesting resource for subsequent valorization.…”
Section: ■ Introductionmentioning
confidence: 99%